OBJEKTIVITAS PEMBERITAAN KASUS PENYERANGAN TERDUGA TERORISME MARKAS KEPOLISIAN DAERAH (MAPOLDA) RIAU DI TRIBUNPEKANBARU.COM - Tika Azaria; Belli Nasution (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Reporting on acts of terror is actually a dilemma. Terrorism is an extraordinary crime that needs to be informed by the mass media because it involves the safety of many people. While on the other hand, terrorism events need a stage to spread threats and fear for the community. So that the mass media, as a source of information, in reporting on incidents of terror must be careful and objective so as not to be biased in information. However, in practice in the field, there are still many mass media that exploit ethnicity and glorification of acts of terror. On May 16, 2018, a terrorist attack took place at Riau Regional Police Headquarters (Mapolda). Many of Riau's local cyber media publish news about this event, one of which is tribunpekanbaru.com, which in quantity presents more news about this act of terror to readers than other cyber media. This study aims to determine the level of objectivity in reporting the case of Riau Regional Police's suspected terrorist attacks in tribunpekanbaru.com.This study uses the theory of objectivity from J. Westerstahl by using a quantitative content analysis method with a descriptive approach. This study is not intended to test certain hypotheses or measure a variable, but merely describes objectivity in a news story. The news samples studied were 58 news in the period 16-20 May 2018. Based on the results of the research that has been conducted, it was concluded that reporting on the case of the alleged attack on Riau Regional Police terrorism in tribunpekanbaru.com, mostly presented objective reporting. From the two dimensions studied, the factuality dimension is quite good from the indicators of truth and indicators of relevance. While the dimensions of impartiality, from the balance indicators of the news are all not delivered proportionally. While the neutrality indicator had been presented quite well.Keywords: The Theory of Objectivity by J. Westerstahl, Content Analysis, News Reporting of Suspected Terrorism of Riau Regional Police Headquarters